Clinical and ultrastructural studies in duodenal pseudomelanosis. Issue 12 (December 1987) - Kang, J Y; Wu, A Y; Chia, J L; Wee, A; Sutherland, I H; Hori, R
Abstract : Nine patients with duodenal pseudomelanosis are described: seven had endstage renal failure while one other patient had undergone renal transplantation. Eight of the nine had been on oral iron supplements. The pigment stained positively with Perls' stain for iron in five patients, positively with the Masson-Fontana method normally used to identify melanin in one, and positively with both methods in three. Electron probe x-ray analysis of the pigment on samples from six patients showed iron to be present in all six, while sulphur was present in five. Varying sulphur content of the pigment in different patients could account for differences in histochemical characteristics. Iron was also shown in the duodenal biopsies of 34 of 48 uraemic patients on oral iron supplements, but was present in only 22 of 120 patients endoscoped for miscellaneous conditions (p less than 0.001). We postulate that the pigment of duodenal pseudomelanosis is derived from iron absorbed from the lumen.